Composition containing chloroprene polymer, molded article, and method for producing molded article
By incorporating a thiol compound with two mercapto groups into the crosslinking process of chloroprene polymers, the environmental concerns associated with traditional accelerators are mitigated, enabling effective crosslinking with reduced ecological impact.
Patent Information
- Application Number
- JP2021570046
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-06
- Filing Date
- 2021-01-05
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-01-05
AI Technical Summary
The existing methods for crosslinking chloroprene polymers use accelerators with high environmental impact, such as ethylene thiourea, which is undesirable due to their environmental effects.
The use of a thiol compound with two mercapto groups per molecule, such as 1,4-bis(3-mercaptobutyryloxy)butane, in combination with chloroprene polymers to facilitate crosslinking, thereby reducing environmental impact.
This approach allows for effective crosslinking of chloroprene polymers with a substance that has a relatively small environmental impact, achieving comparable performance to traditional methods while minimizing ecological harm.
Smart Images

Figure 0007661894000001 
Figure 0007661894000002 
Figure 0007661894000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition containing a chloroprene polymer, a molded article, and a method for producing the molded article. [Background technology]
[0002] Chloroprene crosslinked rubber is used in various applications due to its good general rubber properties, weather resistance, heat resistance, chemical resistance, etc. Chloroprene crosslinked rubber is widely used in civil engineering and construction applications such as expansion joints for highways and bridges, bearing rubber, and vibration-proof rubber materials, as well as in automobile parts and industrial applications. Products using chloroprene crosslinked rubber are superior in weather resistance, heat resistance, and oil resistance compared to products made from other crosslinked rubber materials such as natural rubber or styrene-butadiene rubber, and also have good durability, so that the total cost performance is better than when natural rubber is used, and they are widely used.
[0003] As a related technique, xanthogen-modified chloroprene rubber has been proposed that can achieve both good mechanical strength and elongation fatigue resistance without deteriorating strain resistance and processability at low temperatures (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 110369 Summary of the Invention [Problem to be solved by the invention]
[0005] A crosslinking accelerator is used to produce a chloroprene crosslinked rubber from a chloroprene polymer. Although ethylenethiourea and the like are often used as the crosslinking accelerator, it is desirable to carry out the crosslinking treatment using a substance that has a smaller environmental impact.
[0006] An object of the present invention is to provide a composition that enables crosslinking of chloroprene polymers using substances that have a relatively small environmental impact. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by adding a thiol compound having two mercapto groups per molecule to a chloroprene polymer, instead of a crosslinking accelerator that has a high environmental impact, and have thus completed the present invention. That is, the present invention relates to, for example, the following items [1] to
[10] .
[0008] [1] A composition comprising a chloroprene polymer (A) and a thiol compound (B) having two mercapto groups in one molecule, wherein the amount of the thiol compound (B) is 1.5 parts by mass or more and 20.0 parts by mass or less per 100 parts by mass of the chloroprene polymer (A).
[0009] [2] The composition according to [1], wherein the chloroprene polymer (A) is at least one selected from the group consisting of a homopolymer of chloroprene and a copolymer of chloroprene and another monomer copolymerizable with the chloroprene.
[0010] [3] The composition according to [2], wherein the ratio of the other monomer in the monomers used to form the chloroprene polymer (A) is 30 mass % or less.
[0011] [4] The composition according to any one of [1] to [3], wherein the thiol compound (B) has a primary mercapto group or a secondary mercapto group.
[0012] [5] The composition according to any one of [1] to [4], wherein the thiol compound (B) has two partial structures represented by CH3(SH)CHCH2COOCH2- in one molecule.
[0013] [6] The composition according to any one of [1] to [5], wherein the thiol compound (B) is 1,4-bis(3-mercaptobutyryloxy)butane.
[0014] [7] The composition according to any one of [1] to [6], further comprising a metal oxide. [8] The composition according to [7], wherein the metal oxide is zinc oxide.
[0015] [9] A method for producing a molded article, comprising molding the composition according to any one of [1] to [8] and heating the molded article.
[0016]
[10] A molded article formed using the composition according to any one of [1] to [8]. Effect of the Invention
[0017] It is possible to provide a composition that enables crosslinking of chloroprene polymers using substances that have a relatively small environmental impact. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the configurations of the following embodiments. Each of the components described below can be used alone or in combination.
[0019] [Composition] One embodiment of the composition according to the present invention (hereinafter also referred to as "the composition of this embodiment") contains a chloroprene polymer (A) and a thiol compound (B) having two mercapto groups in one molecule (hereinafter also simply referred to as "thiol compound (B)"). Here, the composition is assumed to be in a form other than latex. Note that latex is a dispersion in which fine particles of a polymer or the like are dispersed in a dispersion medium such as water. For example, a chloroprene polymer latex is a dispersion in which fine particles of a chloroprene polymer (A) are dispersed in a dispersion medium.
[0020] <Chloroprene polymer (A)> The chloroprene polymer (A) may be a homopolymer of 2-chloro-1,3-butadiene (chloroprene) monomer, or may be a copolymer of chloroprene and another monomer copolymerizable with chloroprene (hereinafter also referred to as a "chloroprene copolymer"). A chloroprene homopolymer has no structural units derived from monomers other than chloroprene, whereas a chloroprene copolymer has structural units derived from chloroprene monomers and structural units derived from comonomers, where the comonomer is another monomer copolymerizable with chloroprene.
[0021] Examples of the comonomer include butadiene, butadiene derivatives other than chloroprene, styrene, acrylonitrile, acrylic acid, acrylic acid derivatives, methacrylic acid, and methacrylic acid derivatives. Examples of the butadiene derivatives include alkylated 1,3-butadiene and chlorinated 1,3-butadiene. Examples of the alkylated 1,3-butadiene include isoprene. Examples of the chlorinated 1,3-butadiene include 2,3-dichloro-1,3-butadiene and 1-chloro-1,3-butadiene. Examples of the acrylic acid derivatives include esters of acrylic acid. Examples of the methacrylic acid derivatives include esters of methacrylic acid.
[0022] The proportion of the comonomer in the monomers used to form the chloroprene polymer (A) is preferably 30 mass% or less, more preferably 5 mass% or less, and even more preferably 0 mass%. When the proportion of the comonomer is 30 mass% or less of the monomers used to form the chloroprene polymer (A), the crosslinking treatment can be carried out well.
[0023] When the chloroprene polymer (A) is a chloroprene homopolymer, the crosslinking rate is faster than when the chloroprene polymer (A) is a chloroprene copolymer, and therefore, in order to shorten the crosslinking time, it is preferable to use a chloroprene homopolymer.
[0024] The chloroprene polymer (A) may be any modified chloroprene rubber, such as a sulfur-modified chloroprene rubber, a mercaptan-modified chloroprene rubber, a carboxyl-modified chloroprene rubber, a xanthogen-modified chloroprene rubber, or a mixture of one or more of these.
[0025] <Production method of chloroprene polymer (A) and compounds used in the production> The polymerization method of the monomers when producing the chloroprene polymer (A) is arbitrary, but aqueous emulsion polymerization is preferred. Hereinafter, as an example, a case where the chloroprene polymer (A) is isolated after producing a latex of the chloroprene polymer (A) by aqueous emulsion polymerization will be described. The chloroprene polymer latex may contain additives such as an emulsifier and a chain transfer agent within a range that does not impair the object of the present invention.
[0026] The polymerization temperature during production of the chloroprene polymer (A) is preferably 30° C. or higher, more preferably 33° C. or higher, and particularly preferably 35° C. or higher. The polymerization temperature of the chloroprene polymer (A) is preferably 55° C. or lower, more preferably 50° C. or lower, and particularly preferably 45° C. or lower. A polymerization temperature of 30° C. or higher is preferable because the productivity of the chloroprene polymer (A) is good. A polymerization temperature of 55° C. or lower is very easy because the vapor pressure of chloroprene is low, and the mechanical properties of the obtained polymer, such as tensile strength, are good.
[0027] In producing the chloroprene polymer (A), in addition to the monomers used in the polymerization, an emulsifier, a polymerization initiator, a chain transfer agent, a polymerization terminator, etc. may be used.
[0028] An emulsifier may be added for emulsion polymerization. An anionic surfactant is preferred as the emulsifier. Examples of the anionic surfactant include rosin acid soap, fatty acid soap, sodium salt of naphthalenesulfonic acid condensate, sodium salt of dodecylbenzenesulfonic acid, and sodium salt of dodecylsulfuric acid. When rosin acid soap and fatty acid soap are used together, the solidification operation is simplified, so that rosin acid soap and fatty acid soap may be used as the emulsifier. Examples of rosin acid soap include sodium salt of disproportionated rosin acid and potassium salt of disproportionated rosin acid. Examples of fatty acid soap include oleic acid soap and elaidic acid soap.
[0029] Hereinafter, an example of the amount of the anionic surfactant used will be described, assuming that the total amount of the monomers used to form the chloroprene polymer (A) is 100 parts by mass.
[0030] The amount of the rosin acid soap used, calculated as rosin acid, is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, and even more preferably 0.9 parts by mass or more, and is preferably 8.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 6.0 parts by mass or less.
[0031] The amount of fatty acid soap used is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the total amount of monomers. The amount of fatty acid soap used is preferably 1.0 parts by mass or less, more preferably 0.8 parts by mass or less, and even more preferably 0.7 parts by mass or less, relative to 100 parts by mass of the total amount of monomers used to form the chloroprene polymer (A). If the amount of fatty acid soap used is 0.1 parts by mass or more relative to 100 parts by mass of the total amount of monomers used to form the chloroprene polymer (A), the effect of increasing fluidity is sufficient and is preferable. If the amount of fatty acid soap used is 1.0 parts by mass or less relative to 100 parts by mass of the total amount of monomers used to form the chloroprene polymer (A), it does not precipitate on the dough surface during kneading to make it slippery, or does not remain excessively in the molding machine to cause dirt, and is preferable because it has good processing and operability with rolls, Banbury mixers, etc.
[0032] The amount of the anionic surfactant other than either rosin acid soap or fatty acid soap is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and even more preferably 0.05 parts by mass or more. The amount of the other anionic surfactant other than either rosin acid soap or fatty acid soap is preferably 8.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 6.0 parts by mass or less.
[0033] The particle size of the chloroprene polymer (A) can be adjusted by the amount of the anionic surfactant used. For example, the particle size of the chloroprene polymer (A) can be controlled by the amount of rosin acid soap relative to the monomer during polymerization and the total amount of various emulsifiers. For example, the particle size of the chloroprene polymer (A) tends to be smaller as the amount of the emulsifier increases, and the particle size of the chloroprene polymer (A) tends to be larger as the amount of the emulsifier decreases.
[0034] The polymerization initiator can be selected from general radical polymerization initiators and is not particularly limited. For example, when the chloroprene polymer (A) is produced by emulsion polymerization, peroxides, azo compounds, etc. can be used as the polymerization initiator. The peroxide may be either an organic peroxide or an inorganic peroxide. Examples of peroxides that can be used include benzoyl peroxide, potassium persulfate, ammonium persulfate, etc. Examples of azo compounds that can be used include azobisisobutyronitrile, etc. A combination of two or more radical polymerization initiators can also be used as the polymerization initiator.
[0035] The amount of the polymerization initiator used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, based on 100 parts by mass of the monomer used in the polymerization. The amount of the polymerization initiator used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the monomer used in the polymerization. In addition to the polymerization initiator, one or more types of cocatalysts may be used in combination. Examples of the cocatalyst include anthraquinone sulfonate, potassium sulfite, and sodium sulfite.
[0036] The chain transfer agent can be selected from general chain transfer agents and is not particularly limited. Examples of the chain transfer agent include alkyl mercaptans such as n-dodecyl mercaptan. The amount of the chain transfer agent used is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, based on 100 parts by mass of the monomer used in the polymerization. The amount of the chain transfer agent used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the monomer used in the polymerization.
[0037] The polymerization terminator can be selected from general polymerization terminators and is not particularly limited. The polymerization terminator is added to the system when a predetermined polymerization conversion rate is reached. Examples of the polymerization terminator include phenothiazine, para-t-butylcatechol, hydroquinone, hydroquinone monomethyl ether, and diethylhydroxylamine. The amount of the polymerization terminator added can be any amount that can stop the polymerization reaction.
[0038] The particle size of the chloroprene polymer (A) is preferably 100 nm or more, more preferably 250 nm or more. The particle size of the chloroprene polymer (A) is preferably 500 nm or less, more preferably 450 nm or less. If the particle size of the chloroprene polymer (A) is 100 nm or more and 500 nm or less, stable particles can be formed, which is preferable. The particle size of the chloroprene polymer (A) can be obtained, for example, by measuring a sample obtained by diluting the chloroprene polymer latex or latex composition with pure water using a dynamic light scattering photometer.
[0039] After removing the unreacted monomers in the chloroprene polymer latex, the chloroprene polymer (A) is isolated from the chloroprene polymer latex. Any known method, such as steam stripping, can be used to remove the unreacted monomers. After removing the unreacted monomers, the pH of the chloroprene polymer latex is adjusted to about pH=5 to 7 by adding acetic acid or the like.
[0040] Thereafter, the polymer can be isolated by conventional methods such as freeze coagulation, water washing, and hot air drying. For example, a metal roll (freeze roll) at -10 to -20°C is immersed in the pH-adjusted chloroprene polymer latex and rotated to form a frozen film of the chloroprene polymer (A) on the roll surface. Next, the frozen film is peeled off from the roll surface, and the film is washed with warm water to wash away additives contained in the chloroprene polymer latex, such as emulsifiers, ice, and the like. The film is then passed through a dryer to remove moisture.
[0041] <Thiol compound (B)> The thiol compound (B) contained in the composition of this embodiment has two mercapto groups in one molecule. Although the description in this specification is not intended to be bound by a particular theory, it is speculated that when the thiol compound (B) is heated to a temperature suitable for crosslinking treatment (crosslinking temperature), it reacts with the double bond and chloro group contained in the chloroprene polymer (A) to form a crosslinked structure in the chloroprene polymer (A). In other words, when the thiol compound (B) is heated to the crosslinking temperature, it acts as a film-forming assistant that helps film formation when forming a molded product from the chloroprene polymer (A).
[0042] The thiol compound (B) is not particularly limited as long as it is a compound having two mercapto groups in one molecule. The molecular weight of the thiol compound (B) is preferably 3000 or less, more preferably 2500 or less, and even more preferably 2000 or less. The molecular weight of the thiol compound (B) is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more. The thiol compound (B) may be a reaction product of an aliphatic alcohol and a mercapto-substituted carboxylic acid, or may be a reaction product of a mercapto-substituted alcohol and a carboxylic acid. Here, the carboxylic acid may be either an aliphatic carboxylic acid or an aromatic carboxylic acid.
[0043] Examples of thiol compounds having two primary mercapto groups per molecule include butanediol bis(2-mercaptoacetate), hexanediol bis(2-mercaptoacetate), ethanediol bis(2-mercaptoacetate), 2,2'-(ethylenedithio)diethanethiol, ethylene glycol bis(3-mercapto-2-methylpropionate), propylene glycol bis(3-mercapto-2-methylpropionate), diethylene glycol bis(3-mercapto-2-methylpropionate), butanediol bis(3-mercapto-2-methylpropionate), octanediol bis(3-mercapto-2-methylpropionate), and bis(3-mercapto-2-methylpropyl)phthalate.
[0044] Examples of thiol compounds having two secondary mercapto groups in one molecule include 1,4-bis(3-mercaptobutyryloxy)butane, bis(1-mercaptoethyl)phthalate, bis(2-mercaptopropyl)phthalate, bis(3-mercaptobutyl)phthalate, ethylene glycol bis(3-mercaptobutyrate), propylene glycol bis(3-mercaptobutyrate), diethylene glycol bis(3-mercaptobutyrate), butanediol bis(3-mercaptobutyrate), octanediol bis(3-mercaptobutyrate), ethylene glycol bis(2-mercaptopropionate), propylene glycol bis(2-mercaptopropionate), diethylene glycol bis(2-mercapto propionate), butanediol bis(2-mercaptopropionate), octanediol bis(2-mercaptopropionate), ethylene glycol bis(4-mercaptovalerate), propylene glycol bis(4-mercaptoisovalerate), diethylene glycol bis(4-mercaptovalerate), butanediol bis(4-mercaptovalerate), octanediol bis(4-mercaptovalerate), ethylene glycol bis(3-mercaptovalerate), propylene glycol bis(3-mercaptovalerate), diethylene glycol bis(3-mercaptovalerate), butanediol bis(3-mercaptovalerate), octanediol bis(3-mercaptovalerate), and the like.
[0045] Examples of thiol compounds having two tertiary mercapto groups in one molecule include ethylene glycol bis(2-mercaptoisobutyrate), propylene glycol bis(2-mercaptoisobutyrate), diethylene glycol bis(2-mercaptoisobutyrate), butanediol bis(2-mercaptoisobutyrate), and octanediol bis(2-mercaptoisobutyrate).
[0046] The mercapto group contained in the thiol compound (B) may be any of a primary mercapto group, a secondary mercapto group, and a tertiary mercapto group, but is preferably a primary mercapto group or a secondary mercapto group, and more preferably a secondary mercapto group. In the case of a primary mercapto group or a secondary mercapto group, the steric hindrance is smaller than that of a tertiary mercapto group, so it is considered that the reactivity is better than that of a tertiary mercapto group. The multiple mercapto groups possessed by the thiol compound (B) may be mercapto groups of the same series, or may be mercapto groups of different series. For example, the thiol compound (B) may have a primary mercapto group and a secondary mercapto group.
[0047] The mercapto group may be contained as any partial structure in the molecule, but is preferably contained in the molecule as a partial structure represented by CH3(SH)CHCH2COOCH2-. An example of a suitable thiol having a partial structure represented by CH3(SH)CHCH2COOCH2- is 1,4-bis(3-mercaptobutyryloxy)butane (a specific example of a product is KarenzMT (registered trademark) BD1 manufactured by Showa Denko K.K.).
[0048] When the above-mentioned thiol compound (B) is used to prepare the composition of this embodiment, a molded article having performance equal to or higher than that of a thiourea-based compound such as ethylenethiourea can be produced without using a thiourea-based compound. Here, ethylenethiourea is included in the list of substances of very high concern in the REACH (Registration, Evaluation, Authorization and Restriction of CHemicals) regulation because it exhibits reproductive toxicity. Other thiourea-based compounds also have a high environmental load like ethylenethiourea, and it is desirable to refrain from using them. Therefore, the composition of this embodiment has the advantage that a molded article having a performance equal to or higher than that of a thiourea-based compound can be produced without using a thiourea-based compound having a high environmental load.
[0049] The amount of the thiol compound (B) in the composition is 1.5 parts by mass or more, preferably 1.8 parts by mass or more, and more preferably 1.9 parts by mass or more, relative to 100 parts by mass of the chloroprene polymer (A). When the amount of the thiol compound (B) in the composition is 1.5 parts by mass or more, the time required for the crosslinking treatment is short. In addition, as the crosslinking proceeds, the elasticity of the molded body increases, and the strength at break of the molded body increases. The amount of the thiol compound (B) in the composition is 20.0 parts by mass or less, preferably 15.0 parts by mass or less, and more preferably 11.0 parts by mass or less, relative to 100 parts by mass of the chloroprene polymer (A). When the amount of the thiol compound (B) in the composition is the above-mentioned upper limit value or less, it is preferable because the breaking strength of the molded body does not decrease and the breaking elongation of the molded body does not decrease.
[0050] Other components that may be included in the composition The composition of the present embodiment may further contain a metal oxide, an acid acceptor, a lubricant, an antioxidant, an antioxidant, a stabilizer, a filler, a softener, a processing aid, and a crosslinking accelerator (vulcanization accelerator) within a range that does not impair the object of the present invention.
[0051] The metal oxide can be used to promote crosslinking of the chloroprene polymer (A), and can act as one or more of a crosslinking agent, a crosslinking accelerator, and a crosslinking assistant. For example, magnesium oxide can be used as the metal oxide. In addition to magnesium oxide, examples of the metal oxide include zinc oxide, lead oxide, trilead tetroxide, and calcium oxide. Some of the substances used as the metal oxide also function as an acid acceptor.
[0052] The amount of the metal oxide used in the composition of this embodiment is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, and even more preferably 1.0 parts by mass or more, when the amount of the chloroprene polymer (A) is 100 parts by mass. The amount of the metal oxide used in the composition is preferably 10.0 parts by mass or less, more preferably 9.5 parts by mass or less, and even more preferably 9.0 parts by mass or less, when the amount of the chloroprene polymer (A) is 100 parts by mass. When the amount of the metal oxide used is 0.5 parts by mass or more, the crosslinking speed is sufficient, which is preferable. When the amount of the metal oxide used is 10.0 parts by mass or less, scorching is unlikely to occur, which is preferable.
[0053] An acid acceptor can be used to obtain a good crosslinking rate. Examples of the acid acceptor include magnesium oxide and weakly alkaline inorganic substances, and magnesium oxide is most preferred. Examples of weakly alkaline inorganic substances include hydrotalcite. The amount of the acid acceptor used in the composition of the present embodiment is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, when the chloroprene polymer (A) is taken as 100 parts by mass. The amount of the acid acceptor used in the composition is preferably 6.0 parts by mass or less, more preferably 5.5 parts by mass or less, and even more preferably 5.0 parts by mass or less, when the chloroprene polymer (A) is taken as 100 parts by mass. When the amount of the acid acceptor used in the composition is 0.5 parts by mass or more, the acid acceptance (neutralization) effect is sufficient, which is preferable. When the amount of the acid acceptor used in the composition is 6.0 parts by mass or less, the crosslinking rate is good and desired mechanical properties are easily obtained. Examples of mechanical properties include tensile properties.
[0054] The lubricant is used to reduce frictional resistance with normal processing machines, prevent the composition from sticking to the processing machines, and increase the flowability of the uncrosslinked composition. The lubricant can be selected from common lubricants and is not particularly limited. Examples of the lubricant include fatty acids, fatty acid amides, fatty acid esters, high melting point waxes, low molecular weight polyethylene, and combinations of one or more of them. An example of a fatty acid is stearic acid. An example of a fatty acid amide is stearic acid amide. An example of a fatty acid ester is n-butyl stearate.
[0055] The amount of the lubricant used in the composition of this embodiment is preferably 0.2 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more, when the chloroprene polymer (A) is 100 parts by mass. The amount of the lubricant used in the composition is preferably 3.0 parts by mass or less, more preferably 2.7 parts by mass or less, and even more preferably 2.5 parts by mass or less, when the chloroprene polymer (A) is 100 parts by mass. When the amount of the lubricant used is 0.2 parts by mass or more, adhesion to a molding machine such as a roll can be sufficiently reduced, which is preferable. When the amount of the lubricant used is 3.0 parts by mass or less, the intermolecular force between the polymers is strengthened, which results in improved strength after crosslinking treatment and improved solvent resistance, which is preferable.
[0056] Antiaging agents are broadly classified into antiaging agents added for the purpose of imparting heat resistance (heat-resistant antiaging agents) and antiaging agents added for the purpose of preventing ozone aging (ozone antiaging agents), and it is preferable to use both in combination. As the heat-resistant antiaging agent, a diphenylamine-based antiaging agent is used. The diphenylamine-based antiaging agent is preferable because it not only improves the heat resistance of the chloroprene polymer (A) but also improves mold contamination. Examples of diphenylamine antioxidants include octylated diphenylamine, p-(p-toluenesulfonylamide)diphenylamine, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, etc. Examples of preferred ozone antioxidants include N,N'-diphenyl-p-phenylenediamine (DPPD), N-isopropyl-N'-phenyl-p-phenylenediamine (IPPD), etc.
[0057] The amount of the antiaging agent used in the composition of this embodiment is preferably 1.0 parts by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2.0 parts by mass or more, when the chloroprene polymer (A) is 100 parts by mass. The amount of the antiaging agent used in the composition is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4.0 parts by mass or less, when the chloroprene polymer (A) is 100 parts by mass. When the amount of the antiaging agent used is 1.0 part by mass or more, sufficient antiaging effect is obtained, which is preferable. When the amount of the antiaging agent used is 5.0 parts by mass or less, it is preferable because the crosslinking treatment is not hindered and the mold is less contaminated.
[0058] Although the chloroprene polymer (A) is generally more durable than natural rubber and styrene-butadiene rubber, it is easily deteriorated by oxygen because the polymer contains unsaturated bonds. Therefore, the composition of the present embodiment may contain an antioxidant, a stabilizer, etc., within the scope of not impairing the effects of the invention.
[0059] Examples of the antioxidant include hindered phenol-based antioxidants and amine-based antioxidants. Examples of the hindered phenol-based antioxidants include 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) and 4,4'-methylene-bis(2,6-di-t-butylphenol). Examples of the amine-based antioxidants include alkylated diphenylamines and their derivatives.
[0060] As the stabilizer, for example, an ultraviolet absorbing agent may be used. Examples of the ultraviolet absorbing agent include 2-(5-methyl-2-hydroxyphenyl)benzotriazole.
[0061] The amount of the antioxidant or stabilizer used is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and even more preferably 0.3 parts by mass or more, based on 100 parts by mass of the polymer. The amount of the antioxidant or stabilizer used is preferably 10.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 5.0 parts by mass or less, based on 100 parts by mass of the polymer. If the amount of the antioxidant is within the above range, a sufficient antioxidant effect can be obtained, the crosslinking treatment is not inhibited, and the color tone is not easily deteriorated.
[0062] Examples of the filler include carbon black and other fillers. Examples of grades of carbon black (ASTM (American Society for Testing and Materials) D1765) include FEF grade (Fast Extruding Furnace), SRF grade (Semi-Reinforcing Furnace), HAF grade (High Abrasion Furnace), and ISAF grade (Intermediate Super Abrasion Furnace). One or more of these carbon blacks can be used in the composition. The SRF grade is often used because it has a good balance of mechanical properties and the like of the molded body after crosslinking. The HAF grade is used to further improve the wear resistance of the molded body.
[0063] The amount of carbon black used in the composition is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of the chloroprene polymer (A). The amount of carbon black used in the composition is preferably 120 parts by mass or less, more preferably 110 parts by mass or less, and even more preferably 90 parts by mass or less, based on 100 parts by mass of the chloroprene polymer (A). When the amount of carbon black used is 10 parts by mass or more, the mechanical properties of the molded product are sufficiently improved, which is preferable. When the amount of carbon black used is 120 parts by mass or less, the tensile properties of the molded product are good, and a molded product having compression set resistance, flex resistance, and abrasion resistance is obtained, which is preferable.
[0064] Examples of fillers other than carbon black include silicic anhydride, clay, and especially hard clay, and one or more of these may be used. The amount of the other fillers used is preferably 0.0 to 20.0 parts by mass per 100 parts by mass of the chloroprene polymer (A). When the amount of the other fillers added is 20 parts by mass or less, the molded article has good processability, which is preferable.
[0065] Examples of the softener include naphthenic process oils, aromatic process oils, petroleum process oils, and organic ester process oils. Examples of the organic ester process oils include bis(2-ethylhexyl) phthalate (DOP), bis(2-ethylhexyl) sebacate (DOS), and bis(2-ethylhexyl) azelaate (DOZ). One or more of these process oils may be used in the composition.
[0066] The amount of the softener used is preferably 2.0 parts by mass or more, more preferably 3.0 parts by mass or more, and even more preferably 4.0 parts by mass or more, based on 100 parts by mass of the chloroprene polymer (A). The amount of the softener used is preferably 40.0 parts by mass or less, more preferably 35.0 parts by mass or less, and even more preferably 30.0 parts by mass or less, based on 100 parts by mass of the chloroprene polymer (A). When the amount of the softener used is 2.0 parts by mass or more, the softening effect (plasticization) of the molded body is sufficient, which is preferable. When the amount of the softener used is 40.0 parts by mass or less, the tensile properties and abrasion resistance of the molded body are good, and surface bleeding is unlikely to occur, so that the appearance of the molded body is not easily impaired.
[0067] The processing aid can be selected from general processing aids and is not particularly limited. The processing aid means an additive that improves various molding properties (extrusion, injection, calendaring, etc.) including so-called kneading processability. Examples of the processing aid include stearic acid, waxes, and cis-1,4-polybutadiene, and one or more of these may be used.
[0068] The amount of the processing aid used is preferably 0.2 parts by mass or more, more preferably 0.4 parts by mass or more, and even more preferably 1.0 parts by mass or more, based on 100 parts by mass of the chloroprene polymer (A). The amount of the processing aid used is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4.0 parts by mass or less, based on 100 parts by mass of the chloroprene polymer (A). When the amount of the processing aid used is 0.2 parts by mass or more, sufficient kneading processing is possible, and an improvement effect of molding is obtained, which is preferable. When the amount of the processing aid used is 5.0 parts by mass or less, the mechanical properties such as tensile properties of the molded product are good, and surface bleeding is unlikely to occur, so that the appearance of the molded product is unlikely to be impaired.
[0069] The crosslinking accelerator (vulcanization accelerator) may be selected from crosslinking accelerators generally used for crosslinking chloroprene polymers. Examples of the crosslinking accelerator include dithiocarbamate-based crosslinking accelerators, thiazole-based crosslinking accelerators, thiuram-based crosslinking accelerators, guanidine-based crosslinking accelerators, and xanthogenate-based crosslinking accelerators. Examples of the dithiocarbamate-based crosslinking accelerators include sodium dibutylthiodicarbamate, zinc dibutylthiodicarbamate, and zinc diethylthiodicarbamate. Examples of the thiazole-based crosslinking accelerators include di-2-benzothiazolyl disulfide. Examples of the thiuram-based crosslinking accelerators include tetraethylthiuram disulfide and tetrabutylthiuram disulfide. Examples of the guanidine-based crosslinking accelerators include diphenylguanidine and diorthotoluylguanidine. The amount of the crosslinking accelerator used is preferably 5.0 parts by mass or less, based on 100 parts by mass of the chloroprene polymer (A). From the viewpoint of environmental impact, it is preferable that the composition of the present embodiment does not contain a crosslinking accelerator.
[0070] As an example, the composition can be a composition obtained by blending, relative to 100 parts by mass of the chloroprene polymer (A), 1.5 to 20 parts by mass of the thiol compound (B), 0.5 to 6.0 parts by mass of an acid acceptor, 0.2 to 3.0 parts by mass of a lubricant, 1.0 to 5.0 parts by mass of an antioxidant, 10.0 to 120.0 parts by mass of carbon black, 0 to 20.0 parts by mass of a filler other than carbon black, 2.0 to 40.0 parts by mass of a softener, 0.2 to 5.0 parts by mass of a processing aid, 0.5 to 10.0 parts by mass of a metal oxide, and 0 to 5.0 parts by mass of a vulcanization accelerator.
[0071] <Rubber properties of the composition before crosslinking treatment> The maximum torque value of the composition before crosslinking treatment, measured using a Curastometer Type 7 testing machine in accordance with JIS K6300-2: 2001, is preferably 4.5 or more, more preferably 4.7 or more, and even more preferably 5.0 or more. When the maximum torque value of the composition before crosslinking treatment is 4.5 or more, the balance between the breaking strength and breaking elongation of the molded product obtained by the crosslinking treatment is good, which is preferable. The 90% vulcanization time of the composition before the crosslinking treatment is also called the optimum vulcanization time, and is preferably 45 minutes or less, more preferably 42 minutes or less. If the 90% vulcanization time of the composition before the crosslinking treatment is 45 minutes or less, it is preferable because the time required for the crosslinking treatment is short.
[0072] [Molded body] A molded article can be formed by subjecting the composition of the present embodiment to a crosslinking treatment. The molded article is widely used in, for example, automobile parts, civil engineering and construction, and industrial applications. Civil engineering and construction applications include expansion joints, bearing rubber, and vibration-proof rubber materials. The expansion joints include viaduct expansion joints, highway expansion joints, and bridge expansion joints.
[0073] The molded article is produced, for example, by kneading and molding the composition of the present embodiment containing the chloroprene polymer (A) and the thiol compound (B), and then performing a crosslinking treatment. In the crosslinking treatment, the composition is heated to a desired crosslinking temperature for a desired crosslinking time. The crosslinking temperature is preferably 110°C or higher, more preferably 115°C or higher, and even more preferably 120°C or higher. The crosslinking temperature is preferably 190°C or lower, more preferably 180°C or lower, and even more preferably 170°C or lower. The crosslinking time is preferably 2 minutes or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. The crosslinking time can be preferably 60 minutes or less.
[0074] <Rubber properties of molded products obtained by crosslinking treatment> The modulus (M100) of the molded article at 100% elongation is preferably 1.6 MPa or more, more preferably 1.7 MPa or more, and even more preferably 2.0 MPa or more. If the modulus at 100% elongation is 1.6 MPa or more, it is preferable because the molded article has a desired flexibility. If the modulus at 100% elongation is 4.0 MPa or less, it is preferable because the molded article has high elasticity. The modulus (M300) of the molded article at 300% elongation is preferably 7.0 MPa or more, more preferably 8.0 MPa or more, and even more preferably 8.5 MPa or more. If the modulus at 300% elongation is 7.0 MPa or more, it is preferable because it is possible to achieve both flexibility and elasticity to a degree that can accommodate large deformation. If the modulus at 300% elongation is 12 MPa or less, it is preferable because the elasticity is high. The durometer hardness of the molded article is preferably 50 or more, more preferably 52 or more, and even more preferably 55 or more. If the durometer hardness is 50 or more, it can be evaluated that crosslinking has progressed. The upper limit of the durometer hardness of the molded article may be, for example, 80. The breaking strength of the molded article is preferably 13 MPa or more, more preferably 13.5 MPa or more, and even more preferably 14 MPa or more. If the breaking strength of the molded article is 13 MPa or more, it is preferable in that the crosslinked product is less likely to break. The upper limit of the breaking strength of the molded article may be, for example, 25 MPa. The tensile elongation at break of the molded article is preferably 300% or more, more preferably 350% or more, and even more preferably 400% or more. If the tensile elongation at break of the molded article is 300% or more, it is preferable that the crosslinked product does not break even when it is stretched and used. The upper limit of the tensile elongation at break of the molded article may be, for example, 700%, more preferably 500%. The modulus at 100% elongation, modulus at 300% elongation, durometer hardness, breaking strength, and tensile elongation at break of the molded article were measured by the methods described in the Examples below.
[0075] <Heat resistance of molded products obtained by crosslinking treatment> The absolute value of the difference in durometer hardness between before heating the crosslinked rubber to 100° C. and after keeping it at 100° C. for 70 hours is preferably 25 points or less, more preferably 23 points or less, and even more preferably 21 points or less. If the absolute value of the difference in durometer hardness before and after heating is 25 points or less, it is preferable in terms of maintaining flexibility even in a high-temperature environment.
[0076] The rate of change in breaking strength of the crosslinked rubber (molded article) before heating to 100° C. and after keeping at 100° C. for 70 hours is preferably 30% or less, more preferably 27% or less, and even more preferably 25% or less. If the rate of change in breaking strength before and after heating is 30% or less, the flexibility of the molded article is maintained even after heat treatment, which is preferable in that the molded article is less likely to break. The rate of change in breaking strength is calculated according to formula (1). Rate of change in breaking strength = (X after -X before ) / X before ×100 (1) In formula (1), X before is the breaking strength obtained for the rubber after crosslinking before heating to 100°C. after is the breaking strength obtained after the crosslinked rubber was kept at 100°C for 70 hours.
[0077] The absolute value of the rate of change in tensile elongation at break of the rubber (molded article) after crosslinking treatment represented by the following formula (2) between before heating to 100°C and after keeping at 100°C for 70 hours is preferably 60% or less, more preferably 57% or less, and even more preferably 55% or less. An absolute value of the rate of change in tensile elongation at break of 60% or less is preferable because the molded article is less likely to break even when used in an elongated state. The rate of change of tensile elongation at break is calculated according to formula (2). Change in tensile elongation at break =(Y after -Y before ) / Y before ×100···(2) In formula (2), Y before is the tensile elongation at break obtained for the rubber after crosslinking before heating to 100°C. Y after is the tensile elongation at break obtained after the crosslinked rubber was kept at 100°C for 70 hours. EXAMPLES
[0078] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. In the following description of the examples, "parts" refers to "parts by mass" unless otherwise specified. Furthermore, the numerical values included in the tables showing examples of blend amounts are also parts by mass. First, the methods for measuring and calculating physical properties used in the examples and comparative examples will be explained, and then each example will be described.
[0079] [Methods for measuring physical properties of chloroprene polymer latex and molded products] <Polymerization Conversion Rate of Chloroprene Polymer (A)> The emulsion after the start of polymerization of the chloroprene polymer (A) was collected and dried by standing in an oven at 141°C for 30 minutes to obtain a dry product. The dry product obtained by the drying process contains polymer and solids other than the polymer. Therefore, the mass of the solids other than the polymer was calculated from the amount of the polymerization raw materials charged, and the mass of the dry product obtained by drying the emulsion after polymerization minus the mass of the solids other than the polymer was determined as the "amount of polymer produced," and the polymerization conversion was calculated by formula (3). Polymerization conversion rate [mass%] = [(amount of polymer produced / total amount of monomer charged)] × 100 (3) The "total monomer charge mass" in formula (3) is the sum of the charge amount of chloroprene contained in the amount of emulsion collected to obtain a dry product and the charge amount of comonomer.
[0080] <Rubber characteristics before crosslinking treatment> The test was carried out using a die vulcanization tester conforming to JIS K6300-2:2001, using a Curastometer Type 7 tester. The maximum torque and 90% vulcanization time were measured as rubber properties before crosslinking. To determine the 90% crosslinking time, the crosslinking temperature was set to 160°C, and the crosslinking state was observed while heating for 60 minutes.
[0081] <Evaluation of physical properties of molded products obtained by crosslinking treatment> According to JIS-K6251-2017, the crosslinked sheet was punched out into a No. 3 dumbbell to obtain a test specimen. The sheet test specimen was subjected to a tensile test according to JIS-K6251-2017 to measure the modulus at 100% elongation, the modulus at 300% elongation (M100, M300, respectively), the breaking strength, and the tensile elongation at break at 23°C. The thickness of the test specimen was 2.0 mm. The durometer hardness was measured immediately after pressing the durometer needle against the test specimen according to Type A of JIS-K6253-3:2012. The test specimen used for measuring the durometer hardness was prepared according to the method of collecting and preparing test specimens described in JIS-K-6250-2019.
[0082] Furthermore, in order to examine the heat resistance of the molded article obtained by the crosslinking treatment, the molded article after the crosslinking treatment was kept at 100°C for 70 hours, and then the durometer hardness, breaking strength, and tensile elongation at break were measured.
[0083] [Production Example of Chloroprene Polymer (A)] Into a 5-L reactor, 2.0 kg of 2-chloro-1,3-butadiene (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.04 kg of pure water, 40 g of rosin acid (manufactured by Arakawa Chemical Industries, Ltd., R-300), 2 g of n-dodecyl mercaptan (manufactured by Tokyo Chemical Industry Co., Ltd.), 100 g of a 20 mass% aqueous potassium hydroxide solution (special grade product manufactured by Wako Pure Chemical Industries, Ltd.), 12.8 g of a sodium salt of a β-naphthalenesulfonic acid formalin condensate (manufactured by Kao Corporation), and 6.7 g of a 15 mass% aqueous solution of sodium dodecylbenzenesulfonate (manufactured by Kao Corporation, Neopelex (registered trademark) G-15). The amounts of each substance charged are 52 parts of pure water, 2 parts of rosin acid, 0.1 part of n-dodecyl mercaptan, 1 part of potassium hydroxide, 0.64 parts of sodium salt of β-naphthalenesulfonic acid formalin condensate, and 0.05 parts of sodium dodecylbenzenesulfonate, relative to 100 parts of 2-chloro-1,3-butadiene.
[0084] The starting material charged in the reactor was emulsified, and the rosin acid was converted to rosin acid soap. Then, using 0.3 parts of potassium persulfate (a first-class product manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, polymerization was carried out at a temperature of 40°C for 5 hours under a nitrogen gas atmosphere. The polymerization was stopped when it was confirmed that the polymerization conversion rate was 67% by mass. The polymerization conversion rate was calculated according to formula (1).
[0085] The unreacted monomer was removed by steam distillation to obtain a chloroprene polymer latex. The pH of the chloroprene polymer latex was adjusted to 6.0 by adding acetic acid, and the mixture was subjected to a conventional freeze-coagulation drying method to obtain a chloroprene polymer (A-1).
[0086] Each example will be described below. Table 1 shows the main materials used in the examples and comparative examples other than the chloroprene polymer (A-1).
[0087] [Table 1]
[0088] [Production Example of Mixed Composition A Containing Chloroprene Polymer (A-1)] The materials for the kneaded composition A were mixed in the amounts shown in Table 2, and mixed for 3 minutes at 60 rpm using a Banbury mixer while cooling with water.
[0089] [Table 2]
[0090] [Example 1] The materials were mixed in the amounts shown in the column for Example 1 in Table 3, and mixed for 10 minutes using a 10-inch (25.4 cm) roll under water cooling to give mixed composition B, which was then taken out as a 2 mm thick sheet.
[0091] [Examples 2 to 3, Comparative Examples 1 to 4] Except for the composition of each substance used in the preparation shown in Table 3, the same process as that described in Example 1 was used to prepare the B kneaded composition. In Comparative Example 1, ethylenethiourea was used instead of the thiol compound (B). Furthermore, in Comparative Examples 3 and 4, a thiol containing three or more mercapto groups in one molecule was used instead of the thiol compound (B).
[0092] [evaluation] <Rubber characteristics before crosslinking treatment> The results of tests carried out on the B kneaded compositions obtained in each of Examples 1 to 3 and Comparative Examples 1 to 4 using a Curastometer Type 7 testing machine are shown in Table 3. In addition, MH in Table 3 is the maximum torque value.
[0093] <Preparation of test specimens for evaluating rubber properties after crosslinking treatment> The mixture was crosslinked for 40 minutes in a press molding machine with a mold temperature of 160°C to obtain a sheet with a thickness of 2 mm. In accordance with JIS-K6251-2017, the crosslinked sheet was punched out into a No. 3 dumbbell to obtain a test piece.
[0094] <Rubber properties after crosslinking treatment> The results of measuring the rubber properties after crosslinking treatment for the mixed compositions B obtained in each of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 3. For each composition, the durometer hardness, the modulus at 100% elongation and at 300% elongation (M100, M300, respectively) at 23°C, the breaking strength, and the tensile elongation at break were measured using sheets prepared according to the above-mentioned method for preparing test pieces. The results obtained are shown in Table 3. Furthermore, the crosslinked rubber was kept at 100° C. for 70 hours, after which the durometer hardness, breaking strength, and tensile elongation at break were measured, and the results are also shown in Table 3.
[0095] [Table 3]
[0096] The compositions obtained in all of Examples 1 to 3 showed good values for both the measured values of normal properties and the difference values of properties before and after heating measured to confirm heat resistance. Therefore, it can be said that by using the thiol compound (B) instead of a crosslinking accelerator with a relatively high environmental load such as ethylenethiourea, it is possible to form a rubber material having physical properties equivalent to or greater than those in the case of using a crosslinking accelerator with a relatively high environmental load.
Claims
1. The present invention comprises a chloroprene polymer (A) and a thiol compound (B) having two mercapto groups in one molecule, The thiol compound (B) has a primary mercapto group or a secondary mercapto group, The molecular weight of the thiol compound (B) is 200 or more, The amount of the thiol compound (B) is 1.5 parts by mass or more and 5.0 parts by mass or less based on 100 parts by mass of the chloroprene polymer (A), and the composition is in a form other than a latex.
2. 2. The composition according to claim 1, wherein the chloroprene polymer (A) is at least one selected from the group consisting of a homopolymer of chloroprene and a copolymer of chloroprene and another monomer copolymerizable with the chloroprene.
3. 3. The composition according to claim 2, wherein the ratio of the other monomer in the monomers used to form the chloroprene polymer (A) is 30 mass % or less.
4. The thiol compound (B) is CH 3 (SH)CHCH 2 COOCH 2 The composition according to any one of claims 1 to 3, having two partial structures represented by - in one molecule.
5. The composition according to any one of claims 1 to 4, wherein the thiol compound (B) is 1,4-bis(3-mercaptobutyryloxy)butane.
6. The composition according to any one of claims 1 to 5, further comprising a metal oxide.
7. The composition of claim 6, wherein the metal oxide is zinc oxide.
8. A method for producing a molded article, comprising molding the composition according to any one of claims 1 to 7 and heating the same.
9. A molded article formed using the composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Tire rubber
CN104804245A
Rubber composition
JP1984001546A
Chloropren rubber composition
JP2002138165A
An improved curing system for chlorinated elastomer compositions and a method for curing chlorinated elastomer compositions.
JP2008533281A
Chloroprene polymer composition, and method for producing the same
JP2013177504A